Le tourisme comme enjeu dans la reconstruction post-catastrophe naturelle - Marie Cherchelay (EchoGéo)
Tourism drives the economy of many Caribbean islands. It is the case of Saint-Martin, the French part of the island of Saint Martin (France)/ Sint Maarten (Netherlands). Particularly affected by Hurricane Irma in 2017, Saint Martin is going through a period of reconstruction of its territory and economy. Based on a fieldwork in Saint-Martin, this article focuses on this process, through the prism of tourism. Indeed, tourism allows an analysis of the complex interactions between the involved stakeholders, around the challenges and expectations of the reconstruction period.